Yazoo River basin sedimentation study: cross sectional data - Simons, D. B., author; Li, R. M., author; Brown, G. O., author; Civil Engineering Department, Engineering Research Center, Colorado State University, publisher (Colorado State University. Libraries, 1978)
This manual contains the cross-sectional data used in the Yazoo River Basin Sedimentation Study. The report shows how the complex geometric system has been abstracted to allow simulations of water and sedimentation processes using a physical process mathematical model. This manual also serves as a reference for the existing cross-sectional conditions in the Yazoo River Basin, and to conditions if the proposed plan "E" modifications in addition, are implemented as designed. This manual contains longitudinal river profiles, schematics of cross-sectional locations, lists of cross sections used and plots of the cross sections.
April 1978.
Prepared for U.S. Army Corps of Engineers, Vicksburg District, Vicksburg, Mississippi.
Draft copy.
Keywords: Yazoo River (Miss.); Sedimentation and deposition -- Mississippi -- Yazoo River